Chastotaning o’zgartirish effekti va uning qo’llanilishi - Namazova Hilolaxon Xasanovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
The frequency shift effect, also known as the Doppler effect, is a physical phenomenon that describes the change in wave frequency when the wave source and the observer are in motion. This effect plays a crucial role in acoustics, optics, and radio communication. It is widely used in medical ultrasound diagnostics, the study of galaxy movements in astronomy, and radar systems for determining object velocity. This article explains the concept of the frequency shift effect and highlights its practical applications in various fields.